Public support for policies to improve the nutritional impact of the Supplemental Nutrition Assistance Program (SNAP). Issue 1 (6th December 2012) - Long, Michael W; Leung, Cindy W; Cheung, Lilian WY; Blumenthal, Susan J; Willett, Walter C
Abstract: Objective: To determine public attitudes towards federal spending on nutrition assistance programmes and support for policies to improve the nutritional impact of the Supplemental Nutrition Assistance Program (SNAP). Design: Participants answered survey questions by telephone assessing support for SNAP spending and proposed programme policy changes. Setting: USA. Subjects: Survey of 3024 adults selected by random digit dialling conducted in April 2012, including 418 SNAP participants. Results: A majority (77 %; 95 % CI 75, 79 %) of all respondents supported maintaining or increasing SNAP benefits, with higher support among Democrats (88 %; 95 % CI 86, 90 %) than Republicans (61 %; 95 % CI 58, 65 %). The public supported policies to improve the nutritional impact of SNAP. Eighty-two per cent (95 % CI 80, 84 %) of respondents supported providing additional benefits to programme participants that can only be used on healthful foods. Sixty-nine per cent (95 % CI 67, 71 %) of respondents supported removing SNAP benefits for sugary drinks. A majority of SNAP participants (54 %; 95 % CI 48, 60 %) supported removing SNAP benefits for sugary drinks. Of the 46 % (95 % CI 40, 52 %) of SNAP participants who initially opposed removing sugary drinks, 45 % (95 % CI 36, 54 %) supported removing SNAP benefits for sugary drinks if the policy also included additional benefits to purchase healthful foods. Conclusions: The US public broadly supports increasing or maintaining spending on SNAP. The majority of respondents, including SNAP participants, supported policies to improve the nutritional impact of SNAP by restricting the purchase of sugary drinks and incentivizing purchase of healthful foods with SNAP benefits.